Activity Report: CSV Monitoring and Evaluation - Andrieu, Nadine; Bonilla Findji, Osana (2019)
This progress report focuses on the development, calibration and piloting of one of the components of the CSV Monitoring plan currently been implemented across the CCAFS CSV network, and its integration into the ICT based App developed for data collection purposes.